Perlindungan Hukum Bagi Pekerja Migran Indonesia Korban Kejahatan Perdagangan Orang Dalam Perspektif Hukum Ketenagakerjaan - Prananda, Mayang Talentasari (Media Hukum Indonesia (MHI), 2024)
Indonesia is a legal country that has a relatively large population. Based on data from the Budget Study Center for the Expertise Agency of the Secretariat General of the DPR RI for 2020 to 2024, the number of Indonesian citizens living abroad is recorded at approximately 3,011 (three thousand eleven) million people with 90% being Indonesian migrant workers or often called Indonesian Workers. A person who meets the requirements and qualifications to work abroad for a certain period of time is called an Indonesian Migrant Worker or often understood as an Indonesian Migrant Worker. Indonesian workers still occupy the position as the largest contributor to the country's foreign exchange. Apart from that, there are still many other problems faced by Indonesian workers abroad. One of them is a victim of a human trafficking crime. TPPO or Human Trafficking in the English translation is actually not a recent case. The research method used is normative juridical. Based on the analysis and discussion discussion in this article, it is known that the main factors driving the increase in human trafficking cases are education and the economy. Indonesian workers who are victims of human trafficking are required to receive protection as regulated by the Indonesian Migrant Worker Protection Law.